TBC1D9 and TBC1D9B are ARL8 effectors that modulate exosome secretion through a RAB11A–exocyst pathway - Ganesh Vilas Shelke; Chad D. Williamson; Tal Keren-Kaplan; Juan S. Bonifacino (Proceedings of the National Academy of Sciences, 2026)
Multivesicular endosomes (MVEs) are endolysosomal compartments containing intraluminal vesicles (ILVs) that follow two alternative pathways: fusion with lysosomes, leading to ILV degradation, or fusion with the plasma membrane, resulting in ILV secretion as exosomes. The mechanisms governing this fate decision have only recently begun to be elucidated. Previous work showed that the Biogenesis of lysosome related organelles complex-one-related complex (BORC) and the small guanosine triphosphatase (GTPase) ARL8 promote MVE–lysosome fusion through the ARL8 effector homotypic fusion and protein sorting complex (HOPS), thereby diverting MVEs from exosome secretion. Here, we identify TBC1D9 and TBC1D9B as ARL8 effectors that further suppress exosome release. Acting as GTPase-activating proteins, these proteins drive RAB11A inactivation and dissociation from endolysosomes. This reduces recruitment of the RAB11A effector exocyst complex, preventing MVE fusion with the plasma membrane. These findings thus define a BORC–ARL8–TBC1D9/TBC1D9B axis that further attenuates exosome secretion by blocking MVE–plasma membrane fusion.